Analisis Komprehensif Pengembangan SDM Terhadap Kinerja Karyawan di Rumah Sakit: Literature Review - Hidayati, Wida; Fitriasari, Nur; Widjaja, Yani Restiani (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2024)
Hospitals are business entities that offer intangible services such as health services and rely heavily on Human Resources (HR) for their operations. HR management has a crucial role in driving hospital business. This research aims to understand the importance of HR management in the context of hospital business and the factors that influence it, so that it can improve performance that supports the achievement of organizational goals effectively and efficiently. Increasing company performance can be achieved by maximizing the performance of each individual in the organization. Several factors that have been empirically proven to have a significant effect on employee performance include human resource development, work environment conditions, and organizational commitment. This analysis was carried out through a literature review by reviewing more than 18 relevant journals from Google Scholar, focusing on employee performance theory. The study results show that human resource development, work environment and organizational commitment have a positive impact on employee performance. Therefore, to improve employee performance, organizations or companies must pay full attention to these factors in order to achieve optimal performance.